2011
DOI: 10.1525/auk.2011.11019
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of an endemic Southeast Asian genus: Phylogenetic relationships of the spiderhunters (Nectariniidae:Arachnothera)

Abstract: The phylogeny of spiderhunters (Nectariniidae: Arachnothera) was reconstructed by comparing mitochondrial and nuclear DNA sequences of all currently recognized species and with broad geographic sampling of two particularly variable species complexes, the Little Spiderhunter (Arachnothera longirostra) and the streaky spiderhunters (A. modesta and A. affinis). It appears to be a relatively old group, whose diversification was not caused by recent sea-level changes. However, the modern, highly sympatric distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Although phylogenetic evidence in favor of northern and southern dispersal routes is limited ( Jones & Kennedy 2008, numerous recent analyses have found phylogenetic patterns consistent with island chain-facilitated dispersal along both the western and eastern island arcs, resulting in Philippine populations clearly derived from Sunda Shelf vertebrate groups and often still inhabiting land-bridge islands (Brown & Guttman 2002;Evans et al 2003;Esselstyn et al 2004Jones & Kennedy 2008;Moyle et al 2011Blackburn et al 2013; (Figure 4b). Phylogenetic relationships in fanged frogs (genus Limnonectes; Evans et al 2003) supported the southern colonization route and indicated multiple faunal exchanges, in both directions, between Mindanao and the Indonesian island of Sulawesi (see also , Setiadi et al 2011 (Figure 4b).…”
Section: Recent Arrivals Via Biogeographic Colonization Routesmentioning
confidence: 98%
See 1 more Smart Citation
“…Although phylogenetic evidence in favor of northern and southern dispersal routes is limited ( Jones & Kennedy 2008, numerous recent analyses have found phylogenetic patterns consistent with island chain-facilitated dispersal along both the western and eastern island arcs, resulting in Philippine populations clearly derived from Sunda Shelf vertebrate groups and often still inhabiting land-bridge islands (Brown & Guttman 2002;Evans et al 2003;Esselstyn et al 2004Jones & Kennedy 2008;Moyle et al 2011Blackburn et al 2013; (Figure 4b). Phylogenetic relationships in fanged frogs (genus Limnonectes; Evans et al 2003) supported the southern colonization route and indicated multiple faunal exchanges, in both directions, between Mindanao and the Indonesian island of Sulawesi (see also , Setiadi et al 2011 (Figure 4b).…”
Section: Recent Arrivals Via Biogeographic Colonization Routesmentioning
confidence: 98%
“…Several well-sampled phylogenetic studies demonstrate distinctions between islands with faunas that are phylogenetically clustered (e.g., an island with species stemming from a single common ancestor, or few ancestors) versus islands with faunas that are randomly assembled or phylogenetically overdispersed (species on an island are more closely related to species on other islands than would be expected by chance alone, suggesting ecological processes, environmental filtering, colonization/dispersal, and/or competitive species interactions; Webb et al 2008). Many simple geographic radiations are known, with a single species per island or per PAIC (McGuire & Alcala 2000;Brown & Guttman 2002;Moyle et al 2009Moyle et al , 2011Moyle et al , 2013Siler et al 2010;Esselstyn et al 2011;Welton et al 2013a,b). Many additional complex assemblages are also represented, consisting of multiple distantly related and phenotypically divergent species, consistently observed paired together in a seemingly repeated, deterministic pattern.…”
Section: Community Evolution and Assemblymentioning
confidence: 99%
“…However, floristic analyses of modern plants and several paleoenvironmental studies of floral and faunal assemblages indicate the presence of disjunct rainforest areas in some parts of the Maritime Continent during the LGM, highlighting the possible role of rainforest refugia in establishing the region's ecosystem diversity (Slik et al, 2003;Barton, 2005;Moyle et al, 2011). Evidence for such refugia, coupled with robust evidence for regionally pervasive aridity, suggests significant heterogeneity in past changes in climate and vegetation and highlights important gaps in our understanding of the long-term stability of the regional rainforest ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern, combined with molecular estimates of divergence dates, suggests that Sabah's lowland birds were isolated (one or more times) from populations in western Sundaland, probably in rainforest refugia during global glacial events early in the Pleistocene (e.g., 1-2 million years ago) when most of central Sundaland was subaerial and covered by dry or seasonal forest (Sheldon et al 2015). Similarly, studies suggest that Bornean populations of montane taxa, such as Chloropsis kinabaluensis, Bornean Forktail Enicurus leschenaulti borneensis and Arachnothera everetti, were isolated in rainforest refuges in north-east Borneo from congeneric populations in western Sundaland early in the Pleistocene (Moyle et al 2005(Moyle et al , 2011(Moyle et al , 2017. During the more recent Pleistocene, glaciation events apparently had a different effect on Sundaic habitats; instead of reducing rainforest cover in Sundaland, they increased it, causing greater habitat connectivity among islands and the mainland (Cannon et al 2009, Raes et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Several open-or dry-habitat taxa are shared between Java and Borneo, e.g., Red-breasted Parakeet Psittacula alexandri, Savanna Nightjar Caprimulgus affinis, Copsychus saularis and Scarlet-headed Flowerpecker Dicaeum trochileum (e.g., Mees 1996, Phillipps & Phillipps 2014. More importantly for Meratus populations, preliminary genetic comparisons of some taxa from Borneo's central mountain chain, e.g., swiftlets (Collocalia), spiderhunters (Arachnothera) and forktails (Enicurus), suggest they are closest to Javan populations (Moyle et al 2005(Moyle et al , 2008(Moyle et al , 2011. Thus, it is reasonable to expect that some birds in the Meratus Mountains will have at least as much, or greater, affinity with Javan populations than with other Bornean populations.…”
Section: Discussionmentioning
confidence: 99%